Association analysis of the dopaminergic receptor 2 gene Tag1B rs1079597 and personality traits among a cohort of professional athletes - Michalowska-Sawczyn, M.; Huminska-Lisowska, K.; Chmielowiec, K.; Chmielowiec, J.; Stronska-Pluta, A.; Suchanecka, A.; Zadroga, L.; Massidda, M.; Calò, C. M.; Reclaw, R.; Grzywacz, A. (Biology of Sport, 2025)
Research into sports participation has increasingly pointed to inherent biological mechanisms as influential factors alongside psychosocial and environmental elements. The dopaminergic D2 receptor is a strong candidate gene for physical activity behaviour, given its role in locomotor control and reward mechanisms. Hence, this study aimed to analyse the association of the DRD2 gene Tag1B rs1079597 polymorphism with personality traits in elite athletes. The study group consisted of 395 volunteers. Of these, 163 were professional athletes (22.56±5.9; M = 114, F = 49), and 232 were controls (22.07±4.3; M = 150, F = 82). The MINI-International Neuropsychiatric Interview and the NEO Five-Factor Inventory were administered in both groups. Genotyping was performed using the real-time PCR method. Statistical analysis was performed: genotypes and alleles frequencies were compared using the chi-square test and the relations between DRD2 Tag1B rs1079597 variants, professional athletes and control participants and the NEO Five-Factor Inventory were analysed with the factorial ANOVA. Statistically significant differences were found in the frequency of DRD2 Tag1B rs1079597 genotypes and alleles in the group of professional athletes group compared to the control group. The GG genotype and G allele were significantly more frequent in the group of professional athletes (G/G 0.79 vs G/G 0.66; A/A 0.04 vs A/A 0.03; A/G 0.17 vs A/G 0.31, p = 0.0056; G 0.87 vs. G 0.81; A 0.13 vs. A 0.19, p = 0.0281) compared to the control group. The professional athletes` participants, compared to the controls, obtained significantly higher scores in the assessment of NEO-FFI Extraversion (p = 0.0369) and Conscientiousness (p < 0.0001) scales. Additionally, there was a statistically significant effect of DRD2 rs1079597 genotype association with being a professional athlete on the Openness scale (F2.3389 = 3.07; p = 0.0475; ?2 = 0.015) and on the Conscientiousness scale (F2.3389 = 3.23; p = 0.0406; ?2 = 0.016). This study highlights the significant associations between the DRD2 Taq1B polymorphicsite and personality traitsin a group of professional athletes. It also demonstratesthe association of Taq1B polymorphism and professional sportsmanship with personality traits measured by NEO-FFI. The results suggest that genetic factors and professional sportsmanship both shape an athlete`s personality traits.